A Rare Case of Atypical Myxoid Cellular Neurothekeoma in a 6‐Year‐Old Girl. Issue 2 (21st January 2016) - Han, Tae Young; Han, Byeol; Lee, Young Chae; Lee, June Hyunkyung; Son, Sook‐Ja
Abstract: Neurothekeoma (nerve sheath myxoma)is a benign tumor of probable nerve sheath origin. The atypical cellular variant of this tumor, showing a peculiar histologic pattern, has been very rarely reported in the literature. The atypical variant of cellular neurothekeoma is characterized by features such as large size, deep penetration extending into skeletal muscle and/or subcutaneous fat, diffuse infiltration borders, vascular invasion, high mitotic rate and marked cytologic pleomorphism. We describe a rare form of atypical myxoid cellular neurothekeoma in a 6‐year‐old girl.